LOCAL REVENUE MANAGEMENT AND FINANCIAL PERFORMANCE OF LOCAL GOVERNMENTS: A CASE STUDY OF ATUTUR SUB-COUNTY, KUMI DISTRICT - ASERAIT CHRISTINE (Uganda Christian University, 2025)
The study established the relationship between local revenue management and financial performance in local governments with specific reference to Atutur Sub County, Kumi District. Based on this, three specific objectives were formulated and these are; to examine the relationship between local revenue planning and financial performance Atutur Sub County; to assess the relationship between local revenue collection and financial performance in Atutur Sub County and to determine the relationship between local revenue control and financial performance in Atutur Sub County. This study adopted a case study research design using triangulation approach in which both qualitative and quantitative techniques of data collection were used. The study found out that there is a significant and positive relationship between local revenue planning, local revenue collection, local revenue control and financial performance in Atutur Sub County. It is concluded that an effective and efficient local revenue management is very critical for enhancing financial performance in local governments. Consequently, the study recommends that all the key stakeholders be involved in local revenue planning, collection and the effectuation of a meaningful internal local revenue control mechanisms that will guarantee proper allocation of resources improve financial performance in Atutur sub - County among other local governments.